2004
DOI: 10.1161/01.str.0000130988.44824.29
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Risk of Intracranial Hemorrhage in Patients With Arteriovenous Malformation of the Brain Within a Defined Population

Abstract: Background and Purpose-Accurate estimates for risk and rates of intracranial hemorrhage (ICH)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
143
0
2

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 240 publications
(149 citation statements)
references
References 21 publications
4
143
0
2
Order By: Relevance
“…6,13,14,16,40 Furthermore, recent studies of Halim et al, 14 Yamada et al, 40 da Costa et al, 6 and Hernesniemi et al 15 have shown relatively elevated annual rehemorrhage rates of 5-6% up to 5 years after an initial hemorrhagic presentation.…”
Section: Risk Factors For Hemorrhagementioning
confidence: 97%
“…6,13,14,16,40 Furthermore, recent studies of Halim et al, 14 Yamada et al, 40 da Costa et al, 6 and Hernesniemi et al 15 have shown relatively elevated annual rehemorrhage rates of 5-6% up to 5 years after an initial hemorrhagic presentation.…”
Section: Risk Factors For Hemorrhagementioning
confidence: 97%
“…For the BAVM natural history study, the most valid follow-up model is to use the time from diagnosis to an event. 8,9,31 However, investigators from our study group and other institutes have also reported the hemorrhage rate on the basis of a follow-up method that assumes that the lesion is present from birth and has a subsequent constant annual hemorrhage risk (On-line Table 5). 16,[32][33][34][35] A recent study comparing the 2 approaches suggested that the latter follow-up method is a valid alternative for a BAVM natural history study.…”
Section: Study Limitationsmentioning
confidence: 99%
“…There does not appear to be a gender predilection. They most commonly present with hemorrhage; many population-based studies and large natural history studies demonstrate that approximately 50% of patients present with AVM rupture [40][41][42][43][44][45][46][47][48][49][50][51]. The next most common presenting feature is seizure, with 24-36% of patients presenting with generalized or partial seizures.…”
Section: Clinical Featuresmentioning
confidence: 99%
“…Without treatment, the overall risk of AVM hemorrhage has been estimated to be 2 to 4.6% per year [40][41][42][43][44][45][46]. Previous hemorrhage is a significant risk factor for further hemorrhage; the risk may be as high as 18% in the first year after hemorrhagic presentation [62], returning to baseline within 5 years [63].…”
Section: Prognosismentioning
confidence: 99%